Search for Meaning through the written Word: a discussion of Narrative Methods and their relationship to the Search for Self in Joseph Conrad's Nostromo and Under Western Eyes - Giraud, Cedric H. (My University, 1996)
The primary focus of this thesis will be a formal analysis of narrative methods in Joseph Conrad's Nostromo and Under Western Eyes. Conrad develops the search for an understanding of individual character and selfhood through narrative approaches that self-consciously reflect the thematic and moral tensions in the novels. The metaphysics of alienation on the level of fictional characters are echoed by the epistemological and linguistic scepticism of self-subversive narrative frameworks: the reader's "moral universe" and access to reality are implicitly questioned by the problematic tripartite relationship between characters, the storytellers and shifting degrees of authorial omniscience.
My approach to Conrad combines Bakhtinian critical theory with insights from the theories of Jacques Lacan, whose redefinition of the science of psychoanalysis as a linguistics provides a fascinating analytical framework within which to examine tensions between artistic creativity and the subjective search for meaning through communication.
Keywords: English; English Language and Literature; English Language and Literature